When hunger hurts: a heuristic inquiry into the lived experience of childhood hunger - Barrett, Sarah F. (Kansas State University, 2021)
While the reasons for and consequences of poverty are multifactorial, a lack of money and resources can be insuperable within the family structure. In the United States, hunger is caused by the prevalence of poverty, not food scarcity, and it is this financial circumstance that often forces families to balance the need for food with other basic necessities. In doing so, families often find themselves surviving at diminished levels of food security, wherein accessing adequate food, and the quality, variety, and quantity of their food intake are markedly reduced. Because poverty and food insecurity are household conditions, the occurrence of hunger as an individualized experience is often veiled and largely unacknowledged. Nonetheless, when children experience food insecurity that results in a prolonged, involuntary lack of food that goes beyond the usual uneasy sensation of hunger, a complex trauma can develop. Traumatic experiences, whether witnessed or experienced, often manifest in ways that interfere with emotional or physiological functioning well after the event has ended, and the current study seeks to delve more deeply into the individual experience of childhood hunger using heuristic inquiry. In doing so, the researcher endeavors to tell her story and the stories of others in the United States who have experienced the pervasive and persistent phenomenon, known as childhood hunger. By generating a collective narrative from personal accounts of adults who have experienced hunger as children, discussion of this intractable and well-documented hardship highlights the need for it to be considered as a stand-alone adverse childhood adversity resulting in trauma.
Keywords: Childhood hunger; Adverse childhood experiences (ACE); Heuristic inquiry; Poverty; Complex trauma; Food insecurity